Increased Understanding of Legal Awareness Regarding the Preparation of Written Sales and Purchase Agreements/Contracts in Order to Support Community Economic Activities in Tajun Village, Buleleng Regency - Mangku, Dewa Gede Sudika; Yuliartini, Ni Putu Rai (Institute of Education and Social Research, 2024)
Agreements/contracts are very important in the business world, including in the buying and selling of agricultural and plantation products. In buying and selling transactions for agricultural and plantation products, farmers in carrying out transactions have very little understanding of written sales and purchase agreements and only use verbal agreements and are limited to notes/receipts with middlemen, wholesalers or exporters. There are still many practices that are underhand or carried out without being based on legal agreement/contract documents. The Tajun Village community's understanding of making sales and purchase agreements/contracts is still limited, as a result, activities that should be accompanied by legal documents in the form of agreements/contracts are not yet available. The aim of implementing this community service program is to: (1) increase the understanding of farmer groups in Tajun Village regarding the anatomy of contract agreements and the importance of sales and purchase agreements/contracts (2) train partners' skills in drafting sales and purchase agreements/contracts. The method used in implementing this community service program activity is a pick-up and drop-off system. The results show that the program has been implemented according to plan. From the implementation of this community service program, the target community benefits in the form of increasing partners' understanding regarding legal awareness and written sales and purchase agreements/contracts and being able to draw up simple sales and purchase agreements/contracts in order to support the economic activities of the community in Tajun Village.